Healthcare usage and economic impact of non-treated obesity in Italy: findings from a retrospective administrative and clinical database analysis. Issue 2 (24th February 2017) - Colao, Annamaria; Lucchese, Marcello; D'Adamo, Monica; Savastano, Silvia; Facchiano, Enrico; Veronesi, Chiara; Blini, Valerio; Degli Esposti, Luca; Sbraccia, Paolo
Abstract : Objectives: Investigate the prevalence of obesity in Italy and examine its resource consumption and economic impact on the Italian national healthcare system (NHS). Design: Retrospective, observational and real-life study. Setting: Data from three health units from Northern (Bergamo, Lombardy), Central (Grosseto, Tuscany) and Southern (Naples, Campania) Italy. Participants: All patients aged ≥18 years with at least one recorded body mass index (BMI) measurement between 1 January 2009 and 31 December 2012 were included. Interventions: Information retrieved from the databases included primary care data, medical prescriptions, specialist consultations and hospital discharge records from 2009–2013. Costs associated with these data were also calculated. Data are presented for two time periods (1 year after BMI measurement and study end). Primary and secondary outcome measures: Primary—to estimate health resources consumption and the associated economic impact on the Italian NHS. Secondary—the prevalence and characteristics of subjects by BMI category. Results: 20 159 adult subjects with at least one documented BMI measurement. Subjects with BMI ≥30 kg/m 2 were defined as obese. The prevalence of obesity was 22.2% (N=4471) and increased with age. At the 1-year observation period, obese subjects who did not receive treatment for their obesity experienced longer durations of hospitalisation (median length: 5 days vs 3 days), used more prescription drugs (75.0% vs 57.7%), required more specialised outpatient healthcare (mean number: 5.3 vs 4.4) and were associated with greater costs, primarily owing to prescription drugs and hospital admissions (mean annual cost per year per patient: €460.6 vs €288.0 for drug prescriptions, €422.7 vs € 279.2 for hospitalisations and €283.2 vs €251.7 for outpatient care), compared with normal weight subjects. Similar findings were observed for the period up to data cut-off (mean follow-up of 2.7 years). Conclusions: Untreated obesity has a significant economic impact on the Italian healthcare system, highlighting the need to raise awareness and proactively treat obese subjects.